The Effectiveness Of Productive Infaq-Based Community Economic Empowerment to The Small And Medium Enterprises (SMEs) Growth in Pekalongan - Nur Fani Arisnawati (Ekonomi Syariah IAIN Kudus, 2021)
This study aims to find out (1) the procedure of distributing productive infaq to empower the SMEs’ economy and (2) the effectiveness of productive infaq-based economy empowerment for SMEs growth by BAZNAS through Sharia Financial Institutions in Pekalongan. This research applies a qualitative method using a phenomenology approach, where BAZNAS serves as the primary data. During data collection, this research uses triangulation: observation, interviews, and documentation. Additionally, the sample was selected based on a purposive sampling technique. This study finds out that productive infaq is allocated by sharia financial institutions. Also, the distribution of ZIS (alms and infaq) through the non-profit institutions does not apply profit sharing between BAZNAS and the institutions because it is under qardul hasan. BAZNAS utilizes the productive infaq to increase the capital for business people. If the business has achieved its targets and objectives, the program can be found to be effective. Infaq of Sharia Financial Institutions in 2017-2018 reached 160 million IDR that has been distributed to the SMEs. As a result, the distribution can be considered very effective and may need improvement to get economic growth in Pekalongan.